2021
DOI: 10.1177/15459683211054164
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Treatment Displaying the Missing Leg Improves Phantom Limb Pain: A Small Clinical Trial

Abstract: Background Phantom limb pain (PLP) is a common and in some cases debilitating consequence of upper- or lower-limb amputation for which current treatments are inadequate. Objective This small clinical trial tested whether game-like interactions with immersive VR activities can reduce PLP in subjects with transtibial lower-limb amputation. Methods Seven participants attended 5–7 sessions in which they engaged in a visually immersive virtual reality experience that did not require leg movements (Cool! TM), follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Ambron et al ( 2021 ) conducted a small clinical trial where seven transtibial amputees were exposed to repeated immersive VR gaming activities with a non-embodied control condition and an embodied condition that involved playing games by controlling two intact legs (see Figure 2A ). They found that six of the seven experienced a pain reduction immediately post-session, with an overall reduction over the course of repeated sessions.…”
Section: Neuropathic Pain Conditions and Their Associated Perceptual ...mentioning
confidence: 99%
“…Ambron et al ( 2021 ) conducted a small clinical trial where seven transtibial amputees were exposed to repeated immersive VR gaming activities with a non-embodied control condition and an embodied condition that involved playing games by controlling two intact legs (see Figure 2A ). They found that six of the seven experienced a pain reduction immediately post-session, with an overall reduction over the course of repeated sessions.…”
Section: Neuropathic Pain Conditions and Their Associated Perceptual ...mentioning
confidence: 99%
“…Only one of the studies was an RCT, and the rest were non-randomized, uncontrolled experimental studies. The sample size ranged from 7 14 to 75 15 patients. The etiologies of PLP comprised of upper limb amputation, [16][17][18][19][20][21] lower limb amputation, 14,15,20 and BPA injury.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The sample size ranged from 7 14 to 75 15 patients. The etiologies of PLP comprised of upper limb amputation, [16][17][18][19][20][21] lower limb amputation, 14,15,20 and BPA injury. 17,19,22 Three studies did not follow up with patients in time, 17,19,22 and the most extended follow-up was 6 months posttreatment.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Phantom limb is a persistent sensation of the missing limb experienced in those who undergo amputations. This is a common event, with up to 90% of those who lose a limb experiencing phantom limb at some point (1). Moreover, between 50% and 85% of those with amputations also experience pain located at the missing limb, a condition termed phantom limb pain (PLP) (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Reducing frequency and severity of PLP in these individuals can help restore their function and QOL (11). Currently, the treatments available for PLP include surgical options, non-pharmacologic therapies such as mirror therapy (MT), and pharmacologic intervention (1). However, general consensus is that most current treatment options for PLP show limited evidence of efficacy (1,(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%